2017
DOI: 10.1002/2016jb013704
|View full text |Cite
|
Sign up to set email alerts
|

Seismic attenuation tomography of the source zone of the 2016 Kumamoto earthquake (M 7.3)

Abstract: We study the three‐dimensional seismic attenuation (QP and QS) structure in the source area of the 2016 Kumamoto earthquake (M 7.3) by using 18,296 tP* and 29,668 tS* data from 742 local earthquakes recorded by a dense seismic network consisting of 112 stations deployed in Kyushu Island. Our results show that significant low‐Q (high‐attenuation) anomalies exist in the crust and mantle wedge beneath the volcanic front and back‐arc area, which reflect hot and wet zones caused by convective circulation in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 97 publications
(184 reference statements)
7
34
0
Order By: Relevance
“…In the lower crust, a low-Q P area is widely distributed below the source area. Most recently, Wang et al (2017) also estimated the 3-D attenuation structure in the source region of the 2016 Kumamoto earthquakes and illustrated that the source region of the Kumamoto earthquakes is covered with a high-Q zone in the upper crust underlain by a low-Q zone in the lower crust, which is similar to the present study. Horiguchi and Matsuda (2013) He ratio could be evidence of the high fluid content in the crust.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In the lower crust, a low-Q P area is widely distributed below the source area. Most recently, Wang et al (2017) also estimated the 3-D attenuation structure in the source region of the 2016 Kumamoto earthquakes and illustrated that the source region of the Kumamoto earthquakes is covered with a high-Q zone in the upper crust underlain by a low-Q zone in the lower crust, which is similar to the present study. Horiguchi and Matsuda (2013) He ratio could be evidence of the high fluid content in the crust.…”
Section: Discussionsupporting
confidence: 76%
“…The grid intervals are set to be 0.125° in the lateral directions and 5-50 km along the depth direction. These intervals are smaller than those used by Zhao (2014, 2015), Saita et al (2015), Komatsu and Oda (2015), and Wang et al (2017). For calculation of the ray paths of the Pand S-waves, we employ a 1-D velocity structure, which is based on the JMA2001 model (Ueno et al 2002).…”
Section: Is Rewritten Asmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant seismic velocity variations in the crust and upper mantle beneath the Kumamoto source area have been revealed by many tomographic studies (e.g., Liu & Zhao, , ; J. Wang & Zhao, ; Z. W. Wang et al, ; Yu et al, ; Zhao et al, ). Our results show that the 3‐D velocity model leads to a decrease of the number of inconsistent polarity data and so a better stress inversion result (Figure ), similar to the study of the stress field in the 1994 Northridge earthquake area (Zhao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have generally adopted one‐dimensional (1‐D) seismic velocity models to investigate the stress field in Kyushu (e.g., Matsumoto, Nakao, et al, ; Savage et al, ; Yoshida et al, ). However, many studies of seismic tomography have revealed strong seismic velocity variations in Kyushu, such as low‐velocity anomalies related to the arc magma and fluids in the crust and upper mantle wedge, and the subducting PHS slab that exhibits a strong high‐velocity anomaly (e.g., Liu & Zhao, , ; Z. W. Wang et al, ; Z. Wang & Zhao, , ; J. Wang & Zhao, ; Xia et al, ; Yu et al, ; Zhao, ; Zhao et al, ). The strong seismic velocity variations certainly affect the computation of azimuths and take‐off angles of the P wave rays at the hypocenter, which are required to determine the FMSs and stress tensors using the P wave first‐motion data (e.g., Horiuchi et al, ; Huang et al, ; Zhao et al, ).…”
Section: Introductionmentioning
confidence: 99%